Mathematics Part ii Solutions Solutions for Class 10 Math Chapter 3 Polynomials are provided here with simple step-by-step explanations. These solutions for Polynomials are extremely popular among class 10 students for Math Polynomials Solutions come handy for quickly completing your homework and preparing for exams. All questions and answers from the Mathematics Part ii Solutions Book of class 10 Math Chapter 3 are provided here for you for free. You will also love the ad-free experience on Meritnationâ€™s Mathematics Part ii Solutions Solutions. All Mathematics Part ii Solutions Solutions for class 10 Math are prepared by experts and are 100% accurate.

#### Page No 167:

#### Question 1:

Now in each of the pairs of polynomials given below, check whether the first is a factor of the second:

(i) *x* + 1, *x*^{3} − 1

(ii)* x *− 1, *x*^{3} + 1

(iii) *x* + 1, *x*^{3} + 1

(iv) *x*^{2} − 1, *x*^{4} − 1

(v) *x* − 1, *x*^{4} − 1

(vi) *x* + 1, *x*^{4} − 1

(vii) *x* − 2, *x*^{2} − 5*x* + 1

(viii) *x* + 2, *x*^{2} + 5*x* + 6

(ix)

(x) 1.3*x* − 2.6, *x*^{2} − 5*x* + 6

#### Answer:

(i)

To find whether (*x* + 1) is a factor of (*x*^{3}^{ }− 1), we have to express (*x*^{3}^{ }− 1) in terms of (*x *+ 1).

It can be done as follows:

(*x*^{3}^{ }− 1) = (*x *+ 1)(*ax*^{2} + *bx* + *c*) + *d*

⇒(*x*^{3}^{ }− 1) = *ax*^{3} + *bx*^{2} + *cx* + *ax*^{2} + *bx* + *c* + *d*

⇒(*x*^{3 }− 1) =* ax*^{3} + (*b *+ *a*)*x*^{2} + (*c *+ *b*)*x* + *c* + *d*

For this to hold, we need to equate the coefficients.

We have:

*a* = 1

*b* + *a* = 0

⇒ *b* = −*a* = −1

*c* + *b* = 0

⇒ *c* = −*b* = 1

*c* + *d* = −1

⇒ *d* = −1 − *c* = −1 − 1 = −2

Thus, when (*x*^{3 }− 1) is divided by (*x* + 1), the remainder is −2.

∴ (*x* + 1) is not a factor of (*x*^{3 }− 1).

(ii)

To find whether (*x* − 1) is a factor of (*x*^{3 }+ 1), we have to express (*x*^{3 }+ 1) in terms of (*x *− 1).

It can be done as follows:

(*x*^{3 }+ 1) = (*x *− 1)(*ax*^{2} + *bx* + *c*) + *d*

⇒ (*x*^{3 }+ 1) = *ax*^{3} + *bx*^{2} + *cx* − *ax*^{2} − *bx* − *c* + *d*

⇒ (*x*^{3 }+ 1) =* ax*^{3} + (*b *− *a*)*x*^{2} + (*c *− *b*)*x* − *c* + *d*

For this to hold, we need to equate the coefficients.

We have:

*a* = 1

*b* − *a* = 0

⇒ *b* = *a* = 1

*c* − *b* = 0

⇒ *c* = *b* = 1

−*c* + *d* = 1

⇒ *d* = 1 + *c* = 1 + 1 = 2

Thus, when (*x*^{3 }+ 1) is divided by (*x* −1), the remainder is 2.

∴ (*x* −1) is not a factor of (*x*^{3 }+ 1).

(iii)

To find whether (*x* + 1) is a factor of (*x*^{3 }+ 1), we have to express (*x*^{3 }+ 1) in terms of (*x *+ 1).

It can be done as follows:

(*x*^{3 }+ 1) = (*x *+ 1)(*ax*^{2} + *bx* + *c*) + *d*

⇒ (*x*^{3 }+ 1) = *ax*^{3} + *bx*^{2} + *cx* + *ax*^{2} + *bx* + *c* + *d*

⇒ (*x*^{3 }+ 1) =* ax*^{3} + (*b *+ *a*)*x*^{2} + (*c *+ *b*)*x* + *c* + *d*

For this to hold, we need to equate the coefficients.

We have:

*a* = 1

*b* + *a* = 0

⇒ *b* = −*a* = −1

*c* + *b* = 0

⇒ *c* = −*b* = 1

*c* + *d* = 1

⇒ *d* = 1 − *c* = 1 −1 = 0

Thus, when (*x*^{3 }+ 1) is divided by (*x* +1), the remainder is 0.

∴ (*x* + 1) is a factor of (*x*^{3 }+ 1).

(iv)

To find whether (*x*^{2} − 1) is a factor of (*x*^{4 }− 1), we have to express (*x*^{4 }− 1) in terms of (*x*^{2}* *− 1).

It can be done as follows:

(*x*^{4 }− 1) = (*x*^{2}* *− 1)(*ax*^{2} + *bx* + *c*) + *d*

⇒(*x*^{4 }− 1) = *ax*^{4} + *bx*^{3} + *cx*^{2} − *ax*^{2} − *bx* − *c* + *d*

⇒ (*x*^{4 }− 1) =* ax*^{4} + *bx*^{3} +* *(*c *− *a*)*x*^{2} * *− *bx* − *c* + *d*

For this to hold, we need to equate the coefficients.

We have:

*a* = 1

*b* = 0

*c* − *a* = 0

⇒ *c* = *a* = 1

−*c* + *d* = −1

⇒ *d* = −1 + *c* = −1 + 1 = 0

Thus, when (*x*^{4 }− 1) is divided by (*x*^{2} − 1), the remainder is 0.

∴ (*x*^{2 }− 1) is a factor of (*x*^{4 }− 1).

(v)

To find whether (*x* − 1) is a factor of (*x*^{4 }− 1), we have to express (*x*^{4 }− 1) in terms of (*x *− 1).

It can be done as follows:

(*x*^{4 }− 1) = (*x *− 1)(*ax*^{3} + *bx*^{2} + *cx *+ *d*) + *e*

⇒ (*x*^{4 }− 1) = *ax*^{4} + *bx*^{3} + *cx*^{2} + *dx *− *ax*^{3} − *bx*^{2} − *cx *− *d* + *e*

⇒ (*x*^{4 }− 1) =* ax*^{4} + (*b **−** a*)*x*^{3} + (*c **−** b*)*x*^{2} + (*d **−** c*)*x *− *d* + *e*

For this to hold, we need to equate the coefficients.

We have:

*a* = 1

*b* − *a *= 0

⇒ *b* = *a* = 1

*c* − *b* = 0

⇒ *c* = *b* = 1

*d* − *c* = 0

⇒ *d* = *c* = 1

−*d* + *e* = −1

⇒ *e* = −1 + *d* = −1 + 1 = 0

Thus, when (*x*^{4 }− 1) is divided by (*x *− 1), the remainder is 0.

∴ (*x *− 1) is a factor of (*x*^{4 }− 1).

(vi)

To find whether (*x* + 1) is a factor of (*x*^{4}− 1), we have to express (*x*^{4 }− 1) in terms of (*x *+ 1).

It can be done as follows:

(*x*^{4 }−1) = (*x *+ 1)(*ax*^{3} + *bx*^{2} + *cx *+ *d*) + *e*

⇒ (*x*^{4 }− 1) = *ax*^{4} + *bx*^{3} + *cx*^{2} + *dx *+ *ax*^{3} + *bx*^{2} + *cx *+ *d* + *e*

⇒ (*x*^{4 }− 1) = *ax*^{4} + (*b + a*)*x*^{3} + (*c + b*)*x*^{2} + (*d + c*)*x *+ *d* + *e*

For this to hold, we need to equate the coefficients.

We have:

*a* = 1

*b* + *a *= 0

⇒ *b* = −*a* = −1

*c* + *b* = 0

⇒ *c* = −*b* = 1

*d* + *c* = 0

⇒ *d* = −*c* = −1

*d* + *e* = −1

⇒ *e* = −1 − *d* = −1 + 1 = 0

Thus, when (*x*^{4 }− 1) is divided by (*x* + 1), the remainder is 0.

∴ (*x *+ 1) is a factor of (*x*^{4 }− 1).

(vii)

To find whether (*x* − 2) is a factor of (*x*^{2 }− 5*x* + 1), we have to express (*x*^{2 }− 5*x* + 1) in terms of (*x *− 2).

It can be done as follows:

(*x*^{2 }− 5*x* + 1) = (*x *− 2)(*ax* + *b*) + *c*

⇒ (*x*^{2 }− 5*x* + 1) = *ax*^{2}* *+ *bx *− 2*ax* − 2*b* + *c*

⇒ (*x*^{2 }− 5*x* + 1) =* ax*^{2} + (*b **−** *2*a*)*x* − 2*b* + *c*

For this to hold, we need to equate the coefficients.

We have:

*a* = 1

*b* − 2*a *= −5

⇒ *b* = 2*a* − 5 = 2 − 5 = −3

−2*b *+ *c* = 1

⇒ *c* = 1 + 2*b* = 1 − 6 = −5

Thus, when (*x*^{2 }− 5*x* + 1) is divided by (*x* − 2), the remainder is −5.

∴ (*x* − 2) is not a factor of (*x*^{2 }− 5*x* + 1).

(viii)

To find whether (*x* + 2) is a factor of (*x*^{2 }+ 5*x* + 6), we have to express (*x*^{2 }+ 5*x* + 6) in terms of (*x *+ 2).

It can be done as follows:

(*x*^{2 }+ 5*x* + 6) = (*x *+ 2)(*ax* + *b*) + *c*

⇒ (*x*^{2 }+ 5*x* + 6) = *ax*^{2}* *+ *bx *+ 2*ax* + 2*b* + *c*

⇒ (*x*^{2 }+ 5*x* + 6) =* ax*^{2} + (*b *+ 2*a*)*x* + 2*b* + *c*

For this to hold, we need to equate the coefficients.

We have:

*a* = 1

*b* + 2*a *= 5

⇒ *b* = −2*a* +5 = −2 + 5 = 3

2*b* + *c* = 6

⇒ *c* = 6 − 2*b* = 6 − 6 = 0

Thus, when (*x*^{2 }+ 5*x* + 6) is divided by (*x* + 2), the remainder is 0.

∴ (*x* + 2) is a factor of (*x*^{2 }+ 5*x* + 6).

(ix)

To find whether * * is a factor of (*x*^{2 }− 5*x* + 6), we have to express (*x*^{2 }− 5*x* + 6) in terms of * *.

It can be done as follows:

(*x*^{2 }− 5*x* + 6) = * *(*ax* + *b*) + *c*

⇒ (*x*^{2 }− 5*x* + 6) =

⇒ (*x*^{2 }− 5*x* + 6)

For this to hold, we need to equate the coefficients.

We have:

⇒ *a* = 3

= 5

⇒ *b* = 2*a* + 15 = 6 + 15 = 21

= 6

⇒ 3*c* = 18 + 2*b* = 18 + 42 = 60

Thus, when (*x*^{2 }− 5*x* + 6) is divided by * * the remainder is 60.

∴ is not a factor of (*x*^{2 }− 5*x* + 6).

(x)

To find whether (1.3*x* − 2.6) is a factor of (*x*^{2 }− 5*x* + 6), we have to express (*x*^{2 }−5*x* + 6) in terms of (1.3*x *+ 2.6).

It can be done as follows:

(*x*^{2 }− 5*x* + 6) = (1.3*x *+ 2.6)(*ax* + *b*) + *c*

⇒ (*x*^{2 }− 5*x* + 6) = 1.3*ax*^{2}* *+ 1.3*bx *+ 2.6*ax* + 2.6*b* + *c*

⇒ (*x*^{2 }− 5*x* + 6) =* *1.3*ax*^{2}* *+ (1.3*b *+ 2.6*a*)*x* + 2.6*b* + *c*

For this to hold, we need to equate the coefficients.

We have:

1.3*a* = 1

⇒ *a* =

1.3*b *+ 2.6*a *= −5

⇒ 1.3*b* = −2.6*a* − 5

= −2 −5

= −7

⇒ *b* =

2.6*b* + *c* = 6

⇒ *c* = 6 − 2.6*b* = 6 + 14 = 20

Thus, when (*x*^{2 }− 5*x* + 6) is divided by (1.3*x* − 2.6), the remainder is 20.

∴ (1.3*x* − 2.6) is not a factor of (*x*^{2 }− 5*x* + 6).

#### Page No 170:

#### Question 1:

Check whether each of the polynomials listed below is a factor of 3*x*^{3} − 2*x*^{2} − 3*x* + 2; if not, find the remainder.

(i) *x* − 1

(ii) 3*x* − 2

(iii) 2*x* − 3

(iv) *x* + 1

(v) 3*x* + 2

(vi) 2*x* + 3

#### Answer:

Factor theorem says that for the polynomial *p*(*x*) and for the number *a*, if we have *p*(*a*) = 0 then (*x *− *a*)* *is a factor of *p*(*x*).

Given: Polynomial** **3*x*^{3}^{ }− 2*x*^{2}^{ }− 3*x** *+ 2

(i)

Divisor = (*x* − 1)

Putting *x* = 1 in the given polynomial:

3(1)^{3 }− 2(1)^{2 }− 3(1)* *+ 2

= 3 − 2 − 3 + 2

= 0

∴(*x* − 1) is a factor of the polynomial 3*x*^{3}^{ }− 2*x*^{2}^{ }− 3*x** *+ 2.

(ii)

Divisor = (3*x* − 2)

To check whether (3*x* − 2) is a factor of 3*x*^{3}^{ }− 2*x*^{2}^{ }− 3*x** *+ 2, we have to convert (3*x* −2) in a form that is suitable for the application of the Factor theorem.

(3*x* −2) = 3

Putting *x* = in the given polynomial:

3^{ }− 2^{ }− 3* *+ 2

Thus, _{ }is a factor of the given polynomial.

∴(3*x* −2) is a factor of the polynomial 3*x*^{3 }− 2*x*^{2}^{ }− 3*x** *+ 2.

(iii)

Divisor = (2*x* − 3)

To check whether (2*x* − 3) is a factor of 3*x*^{3}^{ }− 2*x*^{2}^{ }− 3*x** *+ 2, we have to convert (2*x* − 3) in a form that is suitable for the application of the Factor theorem.

(2*x* − 3) = 2

Putting *x* = in the given polynomial:

3^{ }− 2^{ }− 3* *+ 2

=

=

=

Thus, _{ }is a factor of the given polynomial.

∴(2*x* − 3) is not a factor of the polynomial 3*x*^{3}^{ }− 2*x*^{2}^{ }− 3*x** *+ 2.

(iv)

Divisor = (*x* + 1)

To check whether (*x* + 1) is a factor of 3*x*^{3 }− 2*x*^{2 }− 3*x *+ 2, we have to convert (*x* + 1) in a form that is suitable for the application of the Factor theorem.

(*x* + 1) = {*x* − (−1)}

Putting *x* = −1 in the given polynomial:

3(−1)^{3 }− 2(−1)^{2 }− 3(−1)* *+ 2

= −3 − 2 + 3 + 2

= 0

∴(*x* + 1) is a factor of the polynomial 3*x*^{3 }− 2*x*^{2 }− 3*x *+ 2.

(v)

Divisor = (3*x* + 2)

To check whether (3*x* + 2) is a factor of 3*x*^{3 }− 2*x*^{2 }− 3*x *+ 2, we have to convert (3*x* + 2) in a form that is suitable for the application of the Factor theorem.

(3*x* + 2) = 3

= 3

Putting *x* = in the given polynomial:

3^{ }− 2^{ }− 3* *+ 2

=

=

=

_{Thus, } _{ is a factor of the given polynomial.}

∴(3*x* + 2) is not a factor of the expression 3*x*^{3 }− 2*x*^{2 }− 3*x *+ 2.

(vi)

Divisor = (2*x* + 3)

To check whether (2*x* + 3) is a factor of 3*x*^{3 }− 2*x*^{2 }− 3*x *+ 2, we have to convert (2*x* + 3) in a form that is suitable for the application of the Factor theorem.

(2*x* + 3) = 2

= 2

Putting *x* = in the given polynomial:

3^{ }− 2^{ }− 3* *+ 2

=

=

=

_{Thus, } _{is not a factor of the given polynomial.}

∴(2*x* + 3) is not a factor of the polynomial 3*x*^{3 }− 2*x*^{2 }− 3*x *+ 2.

#### Page No 171:

#### Question 1:

What is the remainder on dividing the polynomial *p*(*x*) by *ax* + *b*? What is condition under which *ax* + *b* is a factor of the polynomial *p*(*x*)?

#### Answer:

Remainder theorem states that when a polynomial *p*(*x*) is divided by (*x* − *a*), the remainder obtained is* p*(*a*).

Divisor = *ax* + *b*

*ax* + *b* =

=

The remainder obtained on dividing *p*(*x*) by is.

Thus, the remainder obtained on dividing *p*(*x*) by* ax* + *b* is.

Factor theorem says that for the polynomial *p*(*x*) and for the number *a*, if we have *p*(*a*) = 0, then (*x *− *a*)* *is a factor of *p*(*x*).

For (*ax* + *b*) to be a factor of the polynomial *p*(*x*), *p * should be equal to 0.

#### Page No 171:

#### Question 2:

Is *x* − 1 a factor of *x*^{100} − 1? What about *x* + 1?

#### Answer:

Factor theorem says that for the polynomial *p*(*x*) and for the number *a*, if we have *p*(*a*) = 0, then (*x *− *a*)* *is a factor of *p*(*x*).

Given: Polynomial *x*^{100}^{ }− 1.

Divisor = (*x* − 1)

Putting *x* = 1 in the given polynomial:

(1)^{100 }− 1

= 1 − 1

= 0

∴(* x* − 1) is a factor of the polynomial *x*^{100}^{ }− 1.

Similarly, checking for (*x *+ 1).

To check whether (*x* + 1) is a factor of *x*^{100}^{ }− 1, we have to convert (*x* + 1) in a form that is suitable for the application of the Factor theorem.

(*x *+ 1) = {*x* − (−1)}

Putting *x* = −1 in the given polynomial:

(−1)^{100 }− 1

= 1 − 1

= 0

∴(* x* + 1) is also a factor of the polynomial *x*^{100}^{ }− 1.

#### Page No 171:

#### Question 3:

Is *x* − 1 a factor of *x*^{101} − 1? What about *x* + 1?

#### Answer:

Factor theorem says that for the polynomial *p*(*x*) and for the number *a*, if we have *p*(*a*) = 0, then (*x *− *a*)* *is a factor of *p*(*x*).

Given: Polynomial *x*^{101}^{ }− 1

Divisor = (*x* − 1)

Putting *x* = 1 in the given polynomial:

(1)^{101 }− 1

= 0

∴(* x* − 1) is a factor of the polynomial *x*^{101}^{ }− 1.

Similarly, checking for *x *+ 1.

To check whether (*x* + 1) is a factor of *x*^{101}^{ }− 1, we have to convert (*x* + 1) in a form that is suitable for the application of the Factor theorem.

(*x* + 1) = {*x* − (−1)}

Putting *x* = −1 in the given polynomial:

(−1)^{101 }− 1

= −1 − 1

= −2

∴(* x* + 1) is not a factor of the polynomial *x*^{101}^{ }− 1.

#### Page No 171:

#### Question 4:

Prove that *x* − 1 is a factor of *x*^{n} − 1 for every natural number *n*.

#### Answer:

*p*(*x*) and for the number *a*, if we have *p*(*a*) = 0, then (*x *− *a*)* *is a factor of *p*(*x*).

Given: Polynomial *x*^{n}^{ }− 1

Divisor = (*x* − 1)

Putting *x* = 1 in the given polynomial:

(1)^{n }− 1

= 1 − 1 { (1)^{n} = 1, for all natural numbers *n*}

= 0

∴(* x* − 1) is a factor of the polynomial *x*^{n}^{ }− 1 for every natural number *n*.

#### Page No 171:

#### Question 5:

Prove that *x* + 1 is a factor of *x*^{n} − 1 for every even number *n*.

#### Answer:

*p*(*x*) and for the number *a*, if we have *p*(*a*) = 0, then (*x *− *a*)* *is a factor of *p*(*x*).

Given: Polynomial *x*^{n}^{ }− 1

Divisor = (*x* + 1)

To check whether (*x* + 1) is a factor of *x*^{n}^{ }− 1, we have to convert (*x* + 1) in a form that is suitable for the application of the Factor theorem.

(*x* + 1) = {*x* − (−1)}

Putting *x* = −1 in the given polynomial:

(−1)^{n }− 1

= 1 − 1 { (−1)^{n} = 1, for every even number *n*}

= 0

∴(* x* + 1) is a factor of the polynomial *x*^{n}^{ }− 1 for every even number *n*.

#### Page No 171:

#### Question 6:

Prove that *x* + 1 is a factor of *x*^{n} − 1 for every odd number *n*.

#### Answer:

*p*(*x*) and for the number *a*, if we have *p*(*a*) = 0, then (*x *− *a*)* *is a factor of *p*(*x*).

Given: Polynomial *x*^{n}^{ }− 1

Divisor = (*x* + 1)

To check whether (*x* + 1) is a factor of *x*^{n}^{ }− 1, we have to convert (*x* + 1) in a form that is suitable for the application of the Factor theorem.

(*x* + 1) = {(*x* − (−1)}

Putting *x* = −1 in the given polynomial:

(−1)^{n }− 1

= −1 − 1 ( (−1)^{n} = −1, for every odd number *n*)

= −2

∴(* x* + 1) is a factor of the polynomial *x*^{n}^{ }− 1 for every odd number *n*.

#### Page No 171:

#### Question 7:

What number added to 3*x*^{3} − 2*x*^{2} + 5*x* given a polynomial for which *x* − 1 is a factor?

#### Answer:

Let the number that has to be added to the polynomial 3*x*^{3}− 2*x*^{2} + 5*x* be *c*.

So, the polynomial is 3*x*^{3}− 2*x*^{2} + 5*x* + *c*.

Divisor = (*x* − 1)

*p*(*x*) and for the number *a*, if we have *p*(*a*) = 0, then (*x *− *a*)* *is a factor of *p*(*x*).

Thus, we must have:

3(1)^{3} − 2(1)^{2} + 5(1) + *c* = 0 for (*x* − 1) to be a factor of 3*x*^{3}− 2*x*^{2} + 5*x* + *c*.

⇒ 3 − 2 + 5 + *c* = 0

⇒ *c* = −6

Thus, −6 must be added to 3*x*^{3}− 2*x*^{2} + 5*x* to obtain a polynomial which has (*x *− 1) as a factor.

#### Page No 171:

#### Question 8:

What first degree polynomial added to 3*x*^{3} − 2*x*^{2} gives a polynomial for which both *x* − 1 and *x* + 1 are factors?

#### Answer:

Let the first degree polynomial that has to be added to the polynomial 3*x*^{3}− 2*x*^{2} be *ax* + *b*.

So, the polynomial is 3*x*^{3}− 2*x*^{2} + *ax* + *b*.

Divisor = (*x* − 1)

*p*(*x*) and for the number *a*, if we have *p*(*a*) = 0, then (*x *− *a*)* *is a factor of *p*(*x*).

Thus, we must have:

3(1)^{3} − 2(1)^{2} + *a*(1) + *b* = 0 for (*x* − 1) to be a factor of 3*x*^{3}− 2*x*^{2} + *ax* + *b*.

⇒ 3 − 2 +* a *+ *b* = 0

⇒ *a *+ *b* = −1 …(1)

Similarly, checking for (*x* + 1).

(*x* + 1) = {*x* − (−1)}

We must have:

3(−1)^{3} − 2(−1)^{2} + *a*(−1) + *b* = 0 for (*x* + 1) to be a factor of 3*x*^{3}− 2*x*^{2} + *ax* + *b*.

⇒ −3 − 2 −* a *+ *b* = 0

⇒ *b *− *a* = 5 …(2)

Adding (1) and (2):

2*b* = 4

⇒ *b* = 2

*a* = −3

Therefore, the first degree expression that has to be added to 3*x*^{3}− 2*x*^{2} is −3*x* + 2, so that the polynomial obtained has both (*x* + 1) and (*x* − 1) as the factors.

#### Page No 174:

#### Question 1:

Write each of the polynomial listed below as a product of two first degree polynomials:

(i) 2*x*^{2} + 5*x* + 3

(ii) *x*^{2} + 2*x* − 1

(iii) *x*^{2} + 3*x* + 2

(iv) *x*^{2} − 2

(v) 4*x*^{2} + 20*x* + 25

(vi) *x*^{2} − *x* − 1

#### Answer:

According to the Factor theorem, to find the first degree factors of a polynomial, we need to find those numbers* x*, which make the given polynomial zero.

(i)

The first degree factors of the polynomial 2*x*^{2} + 5*x* + 3 can be obtained by finding out the solutions of the equation 2*x*^{2} + 5*x* + 3 = 0.

_{On comparing with the general quadratic equation, }_{ax}^{2}_{ + bx + c = 0, we have:}

_{a = 2, b = 5 and c = 3}

*x* =

= −1 or

_{So, by the Factor theorem, (x + 1) and } _{are the factors of the given polynomial.}

Now, (*x *+ 1) = *x*^{2} + +

This is not the original polynomial.

We can write:

⇒ (*x *+ 1) =

⇒

⇒

(ii)

The first degree factors of the polynomial *x*^{2} + 2*x* − 1 can be obtained by finding out the solutions of the equation *x*^{2} + 2*x* − 1 = 0.

_{On comparing with the general quadratic equation, }_{ax}^{2}_{ + bx + c = 0, we have:}

_{a = 1, b = 2 and c = −1}

*x* =

= or

_{So, by the Factor theorem, }(*x *+ ) _{and }(*x *+ ) _{are the factors of the given polynomial.}

⇒ (*x *+ ) (*x *+ ) = *x*^{2} + 2*x* − 1

(iii)

The first degree factors of the polynomial *x*^{2} + 3*x* + 2 can be obtained by finding out the solutions of the equation *x*^{2} + 3*x* + 2 = 0.

_{On comparing with the general quadratic equation, }_{ax}^{2}_{ + bx + c = 0, we have:}

_{a = 1, b = 3 and c = 2}

*x* =

=

=

=

= −1 or −2

_{So, by the Factor theorem, (x + 1) and (x + 2) are the factors of the given polynomial.}

⇒ (*x *+ 1) (*x *+ 2) = *x*^{2} + 3*x* + 2

(iv)

The first degree factors of the polynomial *x*^{2} − 2 can be obtained by finding out the solutions of the equation *x*^{2} − 2 = 0.

*x*^{2} − 2 = 0

⇒ (*x* − )(*x* + ) = 0

⇒ *x* = or −

_{So, by the Factor theorem, }(*x *+ ) _{and }(*x *− ) _{are the factors of the given polynomial.}

⇒ (*x *+ )(*x *− ) = *x*^{2} − 2

(v)

The first degree factors of the polynomial 4*x*^{2} + 20*x* + 25 can be obtained by finding out the solutions of the equation 4*x*^{2} + 20*x* + 25 = 0.

_{On comparing with the general quadratic equation, }_{ax}^{2}_{ + bx + c = 0, we have:}

_{a = 4, b = 20 and c = 25}

*x* =

=

=

= −

_{So, by the Factor theorem, } _{and } _{are the factors of the given polynomial.}

Now,

This is not the original polynomial.

We can write:

(vi)

The first degree factors of the polynomial *x*^{2} − *x* − 1 can be obtained by finding out the solutions of the equation *x*^{2} − *x* − 1 = 0.

_{On comparing with the general quadratic equation, }_{ax}^{2}_{ + bx + c = 0, we have:}

_{a = 1, b = −1 and c = −1}

*x* =

=

=

= or

_{So, by the Factor theorem, } _{and } _{are the factors of the given polynomial.}

⇒

#### Page No 174:

#### Question 2:

Prove that none of the polynomials listed below has first degree factors:

(i) *x*^{2} + *x* + 1

(ii) *x*^{4} + 1

(iii) *x*^{2} − *x* + 1

(iv) *x*^{4} + *x*^{2} + 1

#### Answer:

According to the Factor theorem, to find the first degree factors of a polynomial, we need to find those numbers* x*, which make the given polynomial zero.

(i)

The first degree factors of the polynomial *x*^{2} + *x* + 1 can be obtained by finding out the solutions of the equation *x*^{2} + *x* + 1 = 0.

_{On comparing with the general quadratic equation, }_{ax}^{2}_{ + bx + c = 0, we have:}

_{a = 1, b = 1 and c = 1}

⇒ *x* =

As we have obtained a negative value for the discriminant, the polynomial *x*^{2} + *x* + 1 has no first degree factors.

(ii)

The first degree factors of the polynomial *x*^{4} + 1 can be obtained by finding out the solutions of the equation *x*^{4} + 1 = 0.

Let *x*^{2}^{ }= *p*

So, the equation becomes *p*^{2} + 1 = 0.

⇒ *p*^{2} = −1

⇒ *p* =

_{As the value of p is not real, the value of x is also not real.}

Thus, the polynomial *x*^{4} +1 has no first degree factors.

(iii)

The first degree factors of the polynomial *x*^{2} − *x* + 1 can be obtained by finding out the solutions of the equation *x*^{2} − *x* + 1 = 0.

_{On comparing with the general quadratic equation, }_{ax}^{2}_{ + bx + c = 0, we have:}

_{a = 1, b = −1 and c = 1}

⇒ *x* =

As we have obtained a negative value for the discriminant, the polynomial *x*^{2} − *x* + 1 has no first degree factors.

(iv)

The first degree factors of the polynomial *x*^{4} + *x*^{2} + 1 can be obtained by finding out the solutions of the equation *x*^{4} + *x*^{2} + 1 = 0.

Let *x*^{2}^{ }= *p*

⇒ *p*^{2} + *p* + 1 = 0

_{On comparing with the general quadratic equation, }_{ax}^{2}_{ + bx + c = 0, we have:}

_{a = 1, b = 1 and c = 1}

⇒ *p* =

As we have obtained a negative value for the discriminant, the polynomial *x*^{4} + *x*^{2} + 1 has no first degree factors.

View NCERT Solutions for all chapters of Class 10